2008
DOI: 10.1002/jmri.21329
|View full text |Cite
|
Sign up to set email alerts
|

High temporal resolution functional MRI using parallel echo volumar imaging

Abstract: Purpose: To combine parallel imaging with 3D single-shot acquisition (echo volumar imaging, EVI) in order to acquire high temporal resolution volumar functional MRI (fMRI) data. Materials and Methods:An improved EVI sequence was associated with parallel acquisition and field of view reduction in order to acquire a large brain volume in 200 msec. Temporal stability and functional sensitivity were increased through optimization of all imaging parameters and Tikhonov regularization of parallel reconstruction. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 39 publications
0
50
0
Order By: Relevance
“…Standard multislice two-dimensional (2D) -EPI acquires fMRI data at spatial (2-4 mm isotropic) and temporal (2-3 s) resolutions which are sufficient to detect the hemodynamic response to neuronal activations (5). Research from various groups has demonstrated that both functional connectivity based studies (6,7) as well as task-driven fMRI (8,9) benefit from improved statistics attainable with a higher sampling rate. In addition, higher sampling rates allow separation of physiological signal fluctuations and blood oxygenation-level dependent (BOLD) signal of interest (7,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Standard multislice two-dimensional (2D) -EPI acquires fMRI data at spatial (2-4 mm isotropic) and temporal (2-3 s) resolutions which are sufficient to detect the hemodynamic response to neuronal activations (5). Research from various groups has demonstrated that both functional connectivity based studies (6,7) as well as task-driven fMRI (8,9) benefit from improved statistics attainable with a higher sampling rate. In addition, higher sampling rates allow separation of physiological signal fluctuations and blood oxygenation-level dependent (BOLD) signal of interest (7,(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…In such acquisition, the scan time increase would render the sequence more sensitive to intra-scan motion and fat/blood signal regrowth. Echo volumar imaging [34] may help to decrease the scan time of such 3D acquisition, however, its associated low resolution and its robustness against the latter artifacts should be carefully investigated.…”
Section: Limitations Clinical Perspectives and Future Workmentioning
confidence: 99%
“…If one wants to further improve the spatial or temporal resolution, or simply reduce the global imaging time keeping the same acquisition parameters, it would be necessary to increase factor R. To compensate for the intrinsic degradation of the image quality, it is crucial to regularize the reconstruction process which becomes severely ill-posed. To this end, several contributions have been proposed in the recent pMRI literature (Liang et al, 2002;Ying et al, 2004Ying et al, , 2008Lin et al, 2004;Block et al, 2007;Rabrait et al, 2008;Chaâri et al, 2008), most of them operating in the image domain to better estimate full FOV images. For an introductory survey to linear inverse problems with a special emphasis to pMRI reconstruction, the interested reader is referred to Ribes and Schmitt (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Reducing global imaging time is of primary interest in many Magnetic Resonance Imaging (MRI) applications like neuroimaging (Rabrait et al, 2008), cardiac (Weiger et al, 2000) and abdominal (Zhu et al, 2004) imaging since it allows clinicians to limit the patient's exposition to the MRI environment. To achieve this goal without degrading image quality significantly, parallel MRI (pMRI) systems have been developed in the 1990s.…”
Section: Introductionmentioning
confidence: 99%